Evaluation of in-vitro antibiotic susceptibility of different morphological forms of Borrelia burgdorferi - Sapi, Eva (Dove Medical Press, 2011)
BACKGROUND: Lyme disease is a tick-borne illness caused by the spirochete Borrelia burgdorferi. Although antibiotic therapy is usually effective early in the disease, relapse may occur when administration of antibiotics is discontinued. Studies have suggested that resistance and recurrence of Lyme disease might be due to formation of different morphological forms of B. burgdorferi, namely round bodies (cysts) and biofilm-like colonies. Better understanding of the effect of antibiotics on all morphological forms of B. burgdorferi is therefore crucial to provide effective therapy for Lyme disease. METHODS: Three morphological forms of B. burgdorferi (spirochetes, round bodies, and biofilm-like colonies) were generated using novel culture methods. Minimum inhibitory concentration and minimum bactericidal concentration of five antimicrobial agents (doxycycline, amoxicillin, tigecycline, metronidazole, and tinidazole) against spirochetal forms of B. burgdorferi were evaluated using the standard published microdilution technique. The susceptibility of spirochetal and round body forms to the antibiotics was then tested using fluorescent microscopy (BacLight™ viability staining) and dark field microscopy (direct cell counting), and these results were compared with the microdilution technique. Qualitative and quantitative effects of the antibiotics against biofilm-like colonies were assessed using fluorescent microscopy and dark field microscopy, respectively. RESULTS: Doxycycline reduced spirochetal structures ∼90% but increased the number of round body forms about twofold. Amoxicillin reduced spirochetal forms by ∼85%–90% and round body forms by ∼68%, while treatment with metronidazole led to reduction of spirochetal structures by ∼90% and round body forms by ∼80%. Tigecycline and tinidazole treatment reduced both spirochetal and round body forms by ∼80%–90%. When quantitative effects on biofilm-like colonies were evaluated, the five antibiotics reduced formation of these colonies by only 30%–55%. In terms of qualitative effects, only tinidazole reduced viable organisms by ∼90%. Following treatment with the other antibiotics, viable organisms were detected in 70%–85% of the biofilm-like colonies. CONCLUSION: Antibiotics have varying effects on the different morphological forms of B. burgdorferi. Persistence of viable organisms in round body forms and biofilm-like colonies may explain treatment failure and persistent symptoms following antibiotic therapy of Lyme disease.